Identification of alkaloids in methanol extract from leaves of Semenovia suffruticosa when humic substances were added to its root soil in the primary growth - Alireza Sardashti; Mohammadi MS (International Journal of Phytomedicine, 2017)
Alkaloids are a group of natural compounds originally found in plants. Suffruticosa is a species of the genus Semenovia, the Apiaceous family, a native herb in Iran. In this family, alkaloids are found rarely. Humic substances application to the root soil at the beginning of plant growth improves quality, productivity and physical properties of the soil. Accordingly, humic substances were added separately to the root soil of the samples and other samples were selected as the blank plant sample in the distance of 50 cm. Methanol extracts were prepared from dried and powdered leaf samples. The crude alkaloid solution was extracted from methanol extract with 2 % sulfuric acid, dense ammonia and chloroform. The crude alkaloid solution was passed gradiently with mixture solvents of methanol and chloroform through a chromatography column. The output samples of the chromatography column were analyzed by FT-IR, UV-Vis, and TLC and GC-MS techniques. Pyrimido [1, 2-a] quinoxalinone and 1, 3,8-triisopropyl-6-methyl-2,7-naphthyridine alkaloids were identified in both samples and the extracted humic acid (0.513% and 0.979% respectively) and the Sapropel solution (0.449% and 0.678% respectively )were added to their plants soil. Also another alkaloid named 9-benzyloxypyrido [1,2-a]pyrimidin-4-one(9.538%) was identified in the sample and Sapropel was sprayed onto its root soil. No alkaloid was found in the blank plant sample. The results showed that humic substances had considerable effects on the effective substances of the plant Semenovia.suffruticosa.